Assessment of Infection Control among Health Care Workers in Healthcare Centers Sana'a, Yemen : A cross-sectional study - Ameen Saleh Sherah,; Mohd Hasni Jaafar, (Universiti Kebangsaan Malaysia, 2015)
Introduction An Analysis of a Survey Questionnaire on health care workers’ knowledge and practices regarding of infection control and complains them to apply universal precautions. Health care workers are at substantial risk of acquiring blood borne pathogen infections through exposure to blood or other products of patients. To assess of infection control among health care workers in Sana'a healthcare centers, Yemen. Methods A cross-sectional study was conducted in the health center to assess knowledge and practices regarding of infection control among 237 health workers in Sana,a city. A structured self-administered questionnaires were used and data was analyzed using SPSS version 20 and the associations were tested with chi-square, with p-value of < 0.05. Results The health care workers in public centers ware (51.1%) and (48.9%) of them works in private centers. One hundred and seventeen (49.4%) respondents had poor infection control knowledge, 113 (43.5%) had fair knowledge, and 17 (7.2%) had good knowledge. The knowledge was significantly associated with type of center (P < 0.018), such that the public center had the highest proportion with poor knowledge. And nurses and midwife having the highest proportion with fair knowledge of infection control. Eight (3.4%) respondents had a poor practice of universal precautions, 93 (39.2%) had fair practice, and 136 (57.4%) good practice. The practice was significantly associated with the profession, level of education and work experience (P < 0.001), (P < 0.006),P < 0.001) respectively, and nurses and midwives as the profession with the highest proportion with good practice. Conclusion We conclude that the practices and knowledge of universal precautions were low and that's need for intensive programmes to educate health care workers on various aspects of standard precautions and infection control programmes and policies.